If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6m + 2 + -2(m + -1) = 4m + -1(8m + -5) + -9m + 9 Reorder the terms: -6m + 2 + -2(-1 + m) = 4m + -1(8m + -5) + -9m + 9 -6m + 2 + (-1 * -2 + m * -2) = 4m + -1(8m + -5) + -9m + 9 -6m + 2 + (2 + -2m) = 4m + -1(8m + -5) + -9m + 9 Reorder the terms: 2 + 2 + -6m + -2m = 4m + -1(8m + -5) + -9m + 9 Combine like terms: 2 + 2 = 4 4 + -6m + -2m = 4m + -1(8m + -5) + -9m + 9 Combine like terms: -6m + -2m = -8m 4 + -8m = 4m + -1(8m + -5) + -9m + 9 Reorder the terms: 4 + -8m = 4m + -1(-5 + 8m) + -9m + 9 4 + -8m = 4m + (-5 * -1 + 8m * -1) + -9m + 9 4 + -8m = 4m + (5 + -8m) + -9m + 9 Reorder the terms: 4 + -8m = 5 + 9 + 4m + -8m + -9m Combine like terms: 5 + 9 = 14 4 + -8m = 14 + 4m + -8m + -9m Combine like terms: 4m + -8m = -4m 4 + -8m = 14 + -4m + -9m Combine like terms: -4m + -9m = -13m 4 + -8m = 14 + -13m Solving 4 + -8m = 14 + -13m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '13m' to each side of the equation. 4 + -8m + 13m = 14 + -13m + 13m Combine like terms: -8m + 13m = 5m 4 + 5m = 14 + -13m + 13m Combine like terms: -13m + 13m = 0 4 + 5m = 14 + 0 4 + 5m = 14 Add '-4' to each side of the equation. 4 + -4 + 5m = 14 + -4 Combine like terms: 4 + -4 = 0 0 + 5m = 14 + -4 5m = 14 + -4 Combine like terms: 14 + -4 = 10 5m = 10 Divide each side by '5'. m = 2 Simplifying m = 2
| d/dx(ln(18x)) | | 8(3x-4)=25x+218 | | 5[2+4(2x-3)]=25 | | 9x-13=8x+9 | | Ln(4x)=32 | | 12x-20=12-4x | | -38-5x=62-9x | | -13-3x=12+2x | | 15x+9=12x+179 | | 4x+2x-7+9x=5x-x | | 9x-1+4x=90 | | 15-2(w-5)=11 | | 5x-31=2x+17 | | X-18=3x+4 | | 12n^2+15n^3=0 | | 8d+12.4=7-10d | | 9x-2=5(2x+4) | | 2[w-(2w+3)+1]=2(w+2) | | 2x+x^2+1=20.25 | | 3x+4=3(6-x) | | 3f-4-3f=f+4+f | | 4(2-5x)+6=54 | | 11/17 | | (12/x-1)-(16/x)=4 | | 4.20=.75+U | | 4x-3+1=7 | | -4p-5(4-2p)=3(p-6)-23 | | 13x+8=-14x+343 | | 9-5(1-x)=6 | | -(15-3x)=-39 | | 3(x+2)+x=15-(x+4) | | H=10.1+-0.6(3.5) |